An Analysis of Parental Involvement Programs in Teaching-Learning Process during Covid-19 Pandemic - Josuharyadi, Komang; Padmadewi, Ni Nyoman; Suputra, Putu Eka Dambayana (Universitas Pendidikan Ganesha, 2021)
This research aimed to analyze parental involvement programs in the teaching and learning process at Aura Sukma Insani Bilingual Kindergarten during the covid-19 pandemic and the problem faced by the teacher in implementing the parental involvement programs during learning from home because of the covid-19 pandemic at Aura Sukma Insani Bilingual Kindergarten. The parents' involvement programs were analyzed using six types of parental involvement framework proposed by Epstein et al. (2002).Â The present study used an embedded mixed method research design to analyze the school programs involving parents and the problem faced by the teacher in implementing the parental involvement programs. The data were collected using interview, questionnaire, observation, and document analysis. The result of the study showed that (1) there are seven parental involvement programs in Aura Sukma Insani Bilingual Kindergarten, namely; parents conference, parents' interview, final report, online learning, home schooling, virtual field trip, and eco-enzyme (2) there are three problems faced by teacher in implementing the parental involvement programs during the covid-19 pandemic, namely; the connection problems during the online learning, teachers, confusion in dial parents WhatsApp numbers to conduct online learning, and students' mood during online learning.